Effect of polyvinylidene fluoride concentration in PVDF-TiO2-PVP composite membranes properties and its performance in bovine serum albumin rejection - Gayatri, Rianyza; Ahmad Noor Syimir, Fizal; Erna Yuliwati, .; Muhamad Zulhilmi, Zailani; Juhana, Jaafar; Hossain, Md Sohrab; Muzafar, Zulkifli; Taweepreda, Wirach; Ahmad Naim, Ahmad Yahaya (Elsevier Ltd, 2024)
In the present study, the polyvinylidene fluoride (PVDF) was incorporated with polyvinylpyrrolidone (PVP) and titanium dioxide (TiO2) nanoparticles to prepare PVDF-TiO2-PVP composite membrane for Bovine Serum Albumin (BSA) rejection from protein contaminated wastewater. The preparation of PVDF-TiO2-PVP composite membrane was conducted by a non-solvent phase inversion (NIPS) process with varying PVDF weight percentages ranging from 16 to 19 wt%. The polymer concentration plays a critical role in the formation of composite membranes that is commonly overlooked. The primary goal of this study is to examine how the concentration of polymers affects the process of membrane creation, the ensuing structure, and the properties of these membranes. Presently, there is a restricted comprehension concerning the impact of PVDF polymer concentration in the fabrication of membranes using the NIPS approach, particularly for PVDF-TiO2-PVP composite membranes. FE-SEM analysis revealed the lowest skin layer thickness and the number of macro-void formations in a PVDF composite membrane were at 16 wt% PVDF, compared to composite membranes over higher PVDF concentrations from 17 to 19 wt%. There were only slight variations in the percentages of individual elements across all PVDF-TiO2-PVP membranes, yet the values were identical for C, O, F, and Ti. The viscosity was lowest at 16 wt percent PVDF (576.5 MPa s) and greatest at 19 wt percent PVDF (2054.3 MPa s). It showed that 19%wt PVDF viscosity increased fourfold higher than 16%wt. As the concentration of PVDF was increased, a related decrease in the surface porosity of the membrane was observed. The highest hydrophobicity with the contact angle of 79.62° of the composite membranes were detected at 19 wt% of PVDF loading. The maximum water flux (265.43 L/m2h) and BSA flux (250.31 L/m2h) were obtained at 19 wt% of PVDF loading. The lowest PVDF concentration of 16 wt% rejected BSA with 91.01 % efficiency. At 19 wt% PVDF, the rejection rate dropped nearly sixfold to 16.34 %.